A scoping review of “Tang ping” (Lying flat) and mental health status among Chinese youth - Xinrui Ren; Haslinda Abdullah; Hayrol Azril Mohamed Shaffril; Haliza Abdul Rahman; Zeinab Zaremohzzabieh (PLoS ONE, 2026)
"Tang ping" has become a common phenomenon among Chinese youth. The mental health status caused by "Tang ping" has been discussed in many articles, but there has been no scoping review of the research field on "Tang ping" and its mental health status through a complete systematic review procedure. Therefore, this study aims to combine the Preferred Reporting ltems for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidance framework and the Population, Interest, and Context (PlCo) framework to conduct a scoping review on "Tang ping" and its mental health status, to help scholars better conduct follow-up research in this field. The review process included following the review protocol, formulating research questions, and a systematic search strategy based on identification, screening, and eligibility. The main databases covered were China National Knowledge Infrastructure (CNKl), Google Scholar, and Scopus. Of 973 articles, 27 articles were selected. The research results indicated that "Tang Ping" is not a single behavioral pattern, but rather a continuum of coping mechanisms for social stress. Mental health outcomes associated with "Tang Ping" include both negative and positive dimensions, with anxiety, depression, and emotional problems being the most common, accompanied by stress relief and emotional regulation. Differences between students and youth workers highlighted the influence of social context. In conclusion, this scoping review demonstrated that "Tang Ping" is closely associated with mental health through accumulated stress, perceived loss of control, and effort-reward imbalance, and lays a structured foundation for future research in this emerging field.